2015
DOI: 10.18295/squmj.2015.15.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Platelet Counting by Optical and Impedance Methods in Patients with Thrombocytopaenia and Microcytosis

Abstract: The impedance method significantly overestimated platelet counts in microcytic and thrombocytopaenic blood samples. Further attention is therefore needed to improve the accuracy of platelet counts, particularly for patients with conditions associated with microcytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The superiority between the optical and the impedance methods used in the automatic blood analyzers has been a frequently debated topic [19]. Furthermore, a new fluorescence method for platelet detection has aroused the attention of scholars [20].…”
Section: Discussionmentioning
confidence: 99%
“…The superiority between the optical and the impedance methods used in the automatic blood analyzers has been a frequently debated topic [19]. Furthermore, a new fluorescence method for platelet detection has aroused the attention of scholars [20].…”
Section: Discussionmentioning
confidence: 99%
“…The authors compared PLT-O and PLT-F in the study group and found that the correlation between methods was excellent (data not shown). Previous studies [18][19][20] have described good reproducibility and correlation between optical fluorescent platelet counts and IRM, although the populations in these studies did not include patients with thalassemia. Our data confirmed that PLT-O and PLT-F also correlated well with IRM in patients with thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, platelet clumps and giant platelets owing to their large size are not counted as platelets in automated analyzers. All these lead to inaccurate platelet counts in an automated hematology analyzer [8][9][10][11] . Hence platelet count values obtained from automated analyzers should be crosschecked by some other method particularly in cases of thrombocytopenia [12] .…”
Section: Discussionmentioning
confidence: 99%